Vagus nerve stimulation allows to cease maintenance electroconvulsive therapy in treatment-resistant depression: a retrospective monocentric case series - Aboubakr, Oumaima; Domenech, Philippe; Heurtebise, Isabelle; Gaillard, Raphaël; Guy-Rubin, Aurore; Carron, Romain; Duriez, Philibert; Gorwood, Philip; Vinckier, Fabien; Pallud, Johan; Zanello, Marc (Frontiers in Psychiatry, 2024)
The use of vagus nerve stimulation (VNS) to reduce or stop electroconvulsive therapy (ECT) in treatment-resistant depression seems promising. The aim of this study was to investigate the efficacy of VNS on the reduction of ECT sessions and mood stabilization.We conducted a monocentric retrospective case series of patients who suffered from treatmentresistant depression, treated with ECT and referred to our center for VNS. We investigated the number and the frequency of ECT sessions before and after VNS implantation. Secondary criteria consisted in the Montgomery Åsberg Depression Rating Scale (MADRS) score, number of medical treatments, dosage of the main treatment and length of hospital stays before and after VNS. Additionally, we sent an anonymous survey to psychiatrists and other physicians in our institution to investigate their knowledge and perception of VNS therapy to treat treatmentresistant depression.Seven patients benefited from VNS: six (86%) were female (mean age of 51.7 +/-16.0 years at surgery), and five (71%) suffered from bipolar depression (three type I and two type II). All patients were followed up at least two years post-implantation (range: 27-68 months). Prior to VNS, Six patients were treated by maintenance ECT. After VNS, three (43%) patients did not require maintenance ECT anymore, and three (43%) patients required less frequent ECT session with a mean 14.7 +/-9.8 weeks between sessions after VNS vs. 2.9 +/-0.8 weeks before VNS.At last follow-up, 4 (57%) patients had stopped ECT. Five (71%) patients implanted with VNS were good responders (50% decrease relative to baseline MADRS). According to the survey, 4 psychiatrists had a significantly better perception and knowledge of ECT, but a worse perception and knowledge of VNS compared to other physicians.VNS is a good option for treatment-resistant depression requiring maintenance ECT dependance. Larger on-going studies will help broaden the implanted patients while strengthening psychiatrists' knowledge on this therapy.